Mind your state: Insights into antidepressant nonadherence - De Wet Wolmarans; Sarel J. Brand (South African Family Practice, 2016)
Major depressive disorder (MDD) is an insidious disease and affects up to 15% of the global population. Although MDD responds to a wide range of pharmacological treatment options, a number of factors, i.e. not adhering to treatment for at least 4–12 months, contribute to antidepressants not being highly effective. In an attempt to aid clinicians in improving the adherence rates among MDD patients, the current paper will divulge in more detail the possible explanations of why individuals with MDD find it difficult to adhere to prescribed regimens.